Alcohol consumption, physical activity level and body composition of recreational walking practitioners (Research, Society and Development, 2022)
Objective: to analyze alcohol consumption, physical activity level (PAL) and body composition (WC) in recreational walking practitioners. Methods: 125 women and 148 men participated in the study, with a mean age of 37.4 ± 12.8 and 40.0 ± 13.8 years, respectively. The profile of alcohol consumption was evaluated by the Alcohol Use Disorder Identification Test, the NAF by the International Physical Activity Questionnaire-Short Form (IPAQ-SF), for WC, body mass (BM), height was collected, and the height was calculated. body mass index (BMI), and waist circumference (WC) was measured. Descriptive and inferential statistics were applied, adopting p